The Role of Friendship in Mediating and Moderating the Relationship Between Exposure to Gendered Racism and Mental Health among Young Women of Color. - Tao, Xiangyu; Fisher, Celia B. (Journal of Youth & Adolescence, 2025)
Young women of color frequently face discrimination, reflecting the intersecting societal influences of sexism and racism. Although friendships play a significant role in women's lives, there is a lack of research on the role of friendships in navigating exposure to gendered racial discrimination (in-person and social media) and associated mental health. This study investigated the extent to which the content of friendship conversations (i.e., co-rumination against gendered racism, socializing messages related to gendered racial pride and empowerment and oppression awareness) and perceived friendship intimacy and support mediated or moderated the positive association between exposure to gendered racism and mental health. Co-rumination was tested as a mediator, while the other variables were examined as moderators. Online survey data were collected from 339 cisgender women aged 18–24 (M age = 20.90, SD = 1.96; 32.74% Asian, 33.92% Black, and 33.33% Hispanic or Latina; 68.14% identified as straight or heterosexual). Participants described friendship communications and perceived intimacy and support with a same gender and race close friend. Exposure to gendered racial discrimination was significantly associated with depressive and anxiety symptoms and substance use as a coping mechanism. Co-rumination about gendered racism was positively correlated with depressive and anxiety symptoms. Conversely, pride and empowerment socialization was negatively associated with substance use for coping, while oppression awareness socialization was positively correlated with depressive and anxiety symptoms. Structural Equation Modeling Analyses indicated that co-rumination partially mediated the relationship between gendered racism exposure and anxiety symptoms, with other friendship indices not moderating these associations. These findings highlight co-rumination about gendered racism as a risk factor for young women of color and underscore the importance of exploring how the multifaceted nature of friendships is associated with exposure to gendered racism and mental health.